O teorema de Cauchy em equações de Navier-Stokes - Carvalho Junior, Arlindo Dutra (2013)
This work presents the Cauchy's theorem in its classical form, and aims to weaken their hypotheses, providing a more advantageous use in continuum mechanics. The methodology is axiomatic, that is, basic concepts are presented aiming to triggering logical statements that were made in the main theorems to achieve the objectives of this dissertation. The main result is Theorem 14, where a law of balance is folowed necessary and suficient condition for a Cauchy Flow be Weakly Balanced.